Nature of magnetism in Ca 3Co 2O 6 - Wu, Hua; Haverkort, Maurits W. (Physical review letters, 2005)
We find using local spin density approximation+Hubbard U band structure calculations that the novel one-dimensional cobaltate Ca3Co2O6 is not a ferromagnetic half-metal but a Mott insulator. Both the octahedral and the trigonal Co ions are formally trivalent, with the octahedral being in the low-spin and the trigonal in the high-spin state. The inclusion of the spin-orbit coupling leads to the occupation of the minority-spin d2 orbital for the unusually coordinated trigonal Co, producing a giant orbital moment (1.57μB). It also results in an anomalously large magnetocrystalline anisotropy (of order 70 meV), elucidating why the magnetism is highly Ising-like. The role of the oxygen holes, carrying an induced magnetic moment of 0.13μB per oxygen, for the exchange interactions is discussed.
Im Titel sind "3", "2" und "6" tiefgestellt
Gesehen am 08.11.2017